REVOLUTIONARY FORCES AND THE GRUNDNORM: A CRITICAL REVIEW OF THE LEGALITY AND THE RECOGNITION OF NEW CONSTITUTIONAL ORDERS - K.A.A.N. Thilakarathna; G.D.P Madhushan (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
The pure theory of law as advanced by Hans Kelsen endeavour to explain the law as it is pure from the impunities of morality, justice, equity and other types of blurry subject matter. This theory is based on the relationship of norms, where the grundnorm of a given legal system has the ability of empowering all the subsequent norms below it. The constitution, being the supreme law of the country, is recognized as the grundnorm in many of the countries whether you label them as democratic or not. While the change in constitutional order, if done according to the constitutional provisions themselves, if it is done otherwise can pose serious questions related to the legal validity of such a new order. In order to explain this phenomenon, Courts have often made recourse the Kelsen’s pure theory of law. Therefore, this article examines how courts of law in different jurisdictions have use the pure theory of law in explaining the constitutional orders through revolutionary forces.